Selection of inherently safer preventive measures to reduce human error - Wahab, N.A. (Elsevier Ltd, 2016)
The inherent safety concept has been introduced to overcome the shortcoming of traditional hazard assessments by allowing modification to be made at any stage of life-cycle of a process plant. However, most of the proposed inherent safety modifications were suitable to prevent fire, explosion and toxic hazard but less attention on the human factor. Therefore, this paper introduces a technique to assess and improve the preventive measure relevant to human factor aspect using inherent safety concept. Analytic Hierarchy Process model integrated with fuzzy logic known as FAHP was employed to rank the identified inherently safer preventive measures. The model was applied refers to the Piper Alpha offshore disaster with the main intention is to prevent similar incident occurring in the future. The result shows the capability of the proposed methodology in selecting the best inherently safer preventive measure together with its implementation cost and maturity time without requiring lots of precise information to translate experts' opinion from human performance's point of view. Â© 2016 Elsevier Ltd.